Analysis of Alpha CA Genes in Early Vertebrates and ; High-Invertebrates - Seid, Amin Ahmed (fi=Turun yliopisto|en=University of Turku|, 2016)
Carbonic anhydrases are enzymes that are ubiquitously found in all organisms that are engaged in catalyzing the hydration of carbon dioxide to form bicarbonate and proton and vice versa. They are crucial in the process of respiration, bone resorption, pH regulation, ion transport, and photosynthesis in plants. Out of the five classes of carbonic anhydrase α, β, γ, δ, ζ this study focused in the α carbonic anhydrases. This class of CAs constitute of 16 subfamilies in mammals that include 3 non-active enzymes known as Carbonic Anhydrase Related Proteins. The inactiveness of these enzymes is due to the loss of one or more Histidine residues in the active site. This thesis was conducted based on the aim of studying evolutionary analysis of carbonic anhydrase sequences from organisms spanning from the Cambrian age. It was carried out in two phases. The first phase was the sequence collection, which involved many biological sequence databases as a source. The scope of this segment included sequence alignments and analysis of the sequence manually and in an automated form incorporating few analysis tools. The second Phase was phylogenetic analysis and exploring the subcellular location of the proteins, which was key for the evolutionary analysis. Through the medium of the methods conducted with respect to the phases mentioned above, it was possible to accomplish the desired result. Certain thought-provoking sequences were come across and analyzed thoroughly. Whereas, Phylogenetics showed interesting results to bolster previous findings and new findings as well which lay bedrock for future intensified studies.